Basic principle of modern turkey`s policy: “zero problems with neighbors” (Journal of Oriental Studies, 2016)
in turkey the big internal political transformations are changing, especially the last 10 years. authoritarianbureaucratic regime, where the power was in the military it lost their place and value. since 1940 the military have isolated themselves from the public and for many years defended the interests of a certain part society. by reason of their wrong policy the country lacked economic stability and turkey was surrounded on all sides by problems, particularly with its neighbors. at the present stage turkey emphasizes the relationship with the neighbors. in this context, the “zero problems with neighbors” is a short slogan expectation regarding turkey’s relations with neighboring countries. turkey has set a goal to eliminate all the problems in relationship with its neighbors, or it intends at least minimize them. turkey puts this goal at the core of its foreign policy. this approach is a natural reflection of policy stated by the founder of the turkish republic ataturk “Peace in own country is peace in the world”. the author analyzes the results and progress of its conducting policy.
Keywords: turkey; “zero problems with neighbors”